Family caregivers as essential partners in care: examining the impacts of restrictive acute care visiting policies during the COVID-19 pandemic in Canada - Stephanie Montesanti; Gail MacKean; Kayla M. Fitzpatrick; Carol Fancott (BMC, 2023)
Abstract Introduction During the pandemic many Canadian hospitals made significant changes to their 'open family presence' and 'visitor policies' to reduce the spread of COVID-19 by instituting restrictive or 'zero visiting' policies in healthcare facilities. These policies have the potential to create great hardship, anxiety and stress for patients, families, caregivers and frontline healthcare providers (HCPs); along with concerns about the quality and safety of patient care. The presence of family members and other caregivers as essential partners in care is an explicit expression of the philosophy of patient- and family-centred care (PFCC) in action. The purpose of this study is to increase our understanding of how changes to family presence and visiting policies and practices during the COVID-19 pandemic have impacted patients, family caregivers and frontline healthcare providers (HCPs) in acute care hospitals. Methods A total of 38 in-depth semi-structured interviews were conducted with patients, family caregivers and HCPs in Canadian provinces who had experience with visiting policies in acute care settings during the pandemic. COVID patients, and the caregivers of COVID patients, were excluded from this study. A maximum variation sampling strategy was used to guide the selection and recruitment of patients, family caregivers and HCPs, based on our interest in gaining a diversity of perspectives and experiences. Results Many patients, family caregivers, and HCPs view family caregiver presence as integral to PFCC, describing the essential roles played by family caregivers prior to the pandemic. There were commonalities across all three groups with respect to their perspectives on the impacts of restrictive visiting policies on patients, family caregivers and HCPs. They fell into four broad integrated categories: (1) emotional and mental health; (2) communication and advocacy; (3) safety and quality of care; and (4) PFCC, trust in the healthcare system, and future decisions regarding accessing needed healthcare. Recommendations for pandemic visiting policies were also identified. Conclusions The findings from this study highlighted several impacts of restrictive family caregiver presence or visiting policies implemented during COVID-19 on patients, family caregivers and HCPs in acute healthcare settings across Canada. Participants emphasized that there is no "one-size-fits-all" caregiver presence policy that will address all patient needs. To be consistent with the practice of PFCC, patients and family caregivers are welcomed as part of the healthcare team in ways that work for them, demonstrating that flexibility in family presence and visiting policies is essential.